Indonesian Coffee in The Global Value Chain: The Comparison of Global Partnership Sustainability Standards Implementation - Achmad Fadillah; Dikky Indrawan; Noer Azam Achsani (Jurnal Manajemen & Agribisnis, 2019)
Global partnerships based on sustainability standards compiled by international NGOs are needed to achieve social, economic and environmentally sustainable development, as well as to deal with global uncertainty in trade and business of agricultural commodities, including coffee in Indonesia. This paper aims to compare the implementation of global partnership standards in coffee between Indonesia and other producer countries. The Study focused on sustainable standard-compliant in coffee such as 4C and Organic certification standards. Trade and sustainability map tools were described. The findings demonstrate that there were only 8 percent and 9 percent of the Indonesian coffee area certified by 4C and Organic, respectively. Indonesia placed at number fourth of 4C implementation in the worldwide after Brazil, Colombia, and Viet Nam. Indonesia is also placed at number fourth of Organic implementation in the worldwide after Mexico, Ethiopia, and Peru. To compete in the potential market, Indonesia’s commitment to implement sustainable standard-compliant in coffee is needed. Therefore, Indonesia has to increase the coverage of sustainability standards certified area to meet the global market demand. The government also should implement the right policies and programs to enhance the sustainability compliance of national coffee stakeholders.Keywords: coffee, global trade partnership, sustainability standards, global value chain